Satellite temperature measurement in LEO and improvement method of temperature sensors calibration based on the measured data. Issue 7 (10th October 2019) - Sieger, Ladislav; Nentvich, Ondrej; Urban, Martin
Abstract: This article describes the temperature measurement and its calibration on board of the nanosatellite CubeSat class VZLUSAT‐1. There are several thermometers, installed with an analog and a digital output, which are necessary for the accurate measurements calibrations under a vacuum condition or for applying postprocessing corrections. This document describes the way of calibration in a thermal vacuum chamber and its improvement in orbit. In addition, this article will discuss the use of a resistance temperature detector platinum sensors Pt1000 and a digital sensors HYT271 as the reference. A correction variable based on HYT271 compensates a nonlinearity of Pt1000 as well as minimizes the influence of change in a measuring current due to temperature changes. The current correction variable is a function of temperature and nanosatellite's position in the orbit. The measured temperatures are below −70°C in the Earth's shadow and greater than +80°C after irradiation by the Sun. Orbital temperature calibration is performed in two steps. The raw temperature data obtained during the orbital measurement are being used for further improvement. The measurement cycle consists of the electronics calibration, temperature measurement, and temperature calibration. After applying the temperature correction process, the final accuracy becomes better than ±0.15°C.